ANNUAL FLUCTUATION IN THE STABLE CARBON ISOTOPE RATIO OF CORAL SKELETONS: THE RELATIVE INTENSITIES OF KINETIC AND METABOLIC ISOTOPE EFFECTS - Omata T.; Suzuki A.; Kawahat H.; Okamoto M. (My University, 2005)
Stable carbon and oxygen isotope measurements of biogenic carbonate provide information for reconstructing past oceanic environments. In particular, 18O/16O ratios correlate with the temperature and salinity of seawater and 13C/12C is a proxy for dissolved inorganic carbon in seawater and symbiont photosynthesis. Here, we report 13C/12C and 18O/16O values for skeletons of corals (genus Porites) with various growth rates. In faster-growing corals, 13C/12C and 18O/16O showed out-of-phase annual fluctuations. In slower-growing corals, the isotopes fluctuated in phase. We developed a simple vector notation to show two patterns of 13C/12C annual fluctuation, each with a different offset in relation to 18O/16O annual fluctuation. The phase offset between 13C/12C and 18O/16O annual fluctuations depends on the relative intensities of kinetic isotope effects on calcification and metabolic isotope effects such as photosynthesis. This model might improve our ability to infer past climate and oceanographic conditions from coral skeletons.